Robotic Versus Laparoscopic Minimally Invasive Surgery for Rectal Cancer: A Systematic Review and Meta-analysis of Randomized Controlled Trials. Issue 6 (June 2018) - Prete, Francesco Paolo; Pezzolla, Angela; Prete, Fernando; Testini, Mario; Marzaioli, Rinaldo; Patriti, Alberto; Jimenez-Rodriguez, Rosa Maria; Gurrado, Angela; Strippoli, Giovanni F. M.
Abstract : Objective: The aim of this study was to evaluate the safety and efficacy of elective rectal resection for rectal cancer in adults by robotic surgery compared with conventional laparoscopic surgery. Summary of Background Data: Technological advantages of robotic surgery favor precise dissection in narrow spaces. However, the evidence base driving recommendations for the use of robotic surgery in rectal cancer primarily hinges on observational data. Methods: We searched MEDLINE, Embase, and CENTRAL for randomized controlled trials (until August 2016) comparing robotic surgery versus conventional laparoscopic surgery. Data on the following endpoints were evaluated: circumferential margin status, mesorectal grade, number of lymph nodes harvested, rate of conversion to open surgery, postoperative complications, and operative time. Data were summarized as relative risks (RR) or weighted mean differences (WMDs) with 95% confidence intervals (95% CIs). Risk of bias of studies was assessed with standard methods. Results: Five trials were eligible, including 334 robotic and 337 laparoscopic surgery cases. Meta-analysis showed that RS was associated with lower conversion rate (7.3%; 4 studies, 544 participants, RR 0.58; 95% CI 0.35–0.97, P = 0.04, I 2 = 0%) and longer operating time (MD 38.43 minutes, 95% CI 31.84–45.01: P < 0.00001) compared with laparoscopic surgery. Perioperative mortality, rate of circumferential margin involvement (2 studies, 489 participants, RR 0.82, 95% CI 0.39–1.73), and lymph nodes collected (mean 17.4 Lymph Nodes; 5 trials, 674 patients, MD −0.35, 95% CI −1.83 to 1.12) were similar. The quality of the evidence was moderate for most outcomes. Conclusion: Evidence of moderate quality supports that robotic surgery for rectal cancer produces similar perioperative outcomes of oncologic procedure adequacy to conventional laparoscopic surgery. Robotic surgery portraits lower rate of conversion to open surgery, while operating time is significantly longer than by laparoscopic approach. Abstract : Supplemental Digital Content is available in the text